CURRENT TRANSATLANTIC PERSPECTIVES ON SOUTH-EASTERN EUROPE - Florin-Eduard GROSARU (Journal of Defense Resources Management, 2012)
South-Eastern Europe is one of the buffer zones of the current international conflict arena given its role into taking up the jolts stemming both from an old and yet democratic and modern Europe, and from a seething, authoritarian and, in many cases, dogmatic Asia. Within the current international environment characterized by swift and unpredictable changes NATO plays an essential part in strengthening the Euroatlantic security. As a result of the Alliance’s determination to model and ensure a solid security environment and a durable peace, the new NATO doctrine develops a strategic concept according to which security strengthening needs to be based on a political-military partnership, as well as on cooperation and dialogue among all states.